Therapeutic role of isoflavones from traditional medicine in the management of polycystic ovary syndrome - Ashwini Armarkar; Prafulla Sabale; Satyendra Prasad; Vidya Sabale; Lata Potey; Dipti Masram (Pharmacological Research - Modern Chinese Medicine)
Introduction: Polycystic ovary syndrome (PCOS) is a significant public health problem and one of the most common gynaecological and endocrine disorder.This condition affects an estimated 8–13 % of women of reproductive age worldwide. PCOS manifests as a group of symptoms, including oligomenorrhea, obesity, infertility, increased risk of diabetes, acne, and hirsutism. The etiology of PCOS involves a complex interplay of factors, including genetic predisposition, neuroendocrine dysregulation, contemporary lifestyle practices, and obesity. Numerous traditional chinese formulations have demonstrated success in mitigating PCOS symptoms and addressing its underlying causes. Methodology: Online databases such as Google Scholar, PubMed, and ScienceDirect Library were employed to find literatures on “Polycystic ovary syndrome,” “Phytoestrogens,” “Pharmacokinetics of Isoflavones” Role of isoflavones in PCOS. considering articles published in the last 20 years to capture recent research.This review summarizes the scientific findings on traditional herbs rich in isoflavones and their bioactive components of the phytoestrogen class for the management of PCOS. Result: Isoflavones, a subset of polyphenolic compounds, represent a prominent class of phytoestrogens. These secondary plant metabolites, which predominantly occur in the Fabaceae family, exhibit structural similarities to 17β-estradiol, and typically exist in conjugated forms. The estrogenic properties of isoflavone phytoconstituents, such as genistein, biochanin A, daidzein, puerarin, and formononetin, confer substantial therapeutic potential for PCOS management. Conclusion: Despite their therapeutic potential, there is a paucity of data regarding the safety profile, clinical efficacy, and optimal treatment duration of isoflavones. Further investigations across various domains of isoflavone research are imperative to enhance the understanding of this complex field of study.